1996
DOI: 10.2139/ssrn.1815952
|View full text |Cite
|
Sign up to set email alerts
|

Savings in Chile: What Went Right?

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
3

Year Published

1998
1998
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 11 publications
1
14
0
3
Order By: Relevance
“…The same conclusions for Chile are achieved by two other studies although to a different extent. First, Morande () argues that the emergence of private pension funds in Chile had a positive effect on total private saving. To investigate the extent of a positive crowding‐out, that is, the effect of compulsory saving on private voluntary saving, he estimates co‐integrating equations for the latter both in per‐capita values and as a ratio of GDP.…”
Section: Pension Funds and Financial Marketsmentioning
confidence: 99%
“…The same conclusions for Chile are achieved by two other studies although to a different extent. First, Morande () argues that the emergence of private pension funds in Chile had a positive effect on total private saving. To investigate the extent of a positive crowding‐out, that is, the effect of compulsory saving on private voluntary saving, he estimates co‐integrating equations for the latter both in per‐capita values and as a ratio of GDP.…”
Section: Pension Funds and Financial Marketsmentioning
confidence: 99%
“…Using an error correction model, Morande (1996) also finds a significant positive effect of a pension fund dummy on private saving from 1960 to 1995. He speculates that the financial market deepening caused by pension reform may have made voluntary saving less likely to be crowded out by, and therefore less sensitive to fluctuations in, foreign saving, thus making the country's supply of investible resources less dependent on foreign capital.…”
Section: Increased National Savingmentioning
confidence: 90%
“…However, Edwards (1995) notes that, sophisticated financial products like pension asset-backed housing finance have increased the rate of savings. Likewise, Morandé (1998) found that funded pension funds increased savings in Chile which improved the ability of pension fund members to raise down payments for a mortgage.…”
Section: Pension Contribution Performance Informationmentioning
confidence: 99%